KERAGAMAN AMFIBI DAN CATATAN BARU KATAK DI KAWASAN WISATA GUCI, PROVINSI JAWA TENGAH - . Mumpuni (ZOO INDONESIA, 2014)
The study was conducted in tourism area of Guci, Tegal regency, Central Java for 5 days in October 2009. It was revealed that 16 species of frogs and one species of caecilian found in the area. We also obtained an interesting spesies of bleeding frog Leptophryne cruentata, an endemic frog from West Java and Hylarana rufipes that previously only was informed from West Sumatra. Species composition, distribution and abundance is presented.